Evaluation of an internet-based intervention for service members of the German armed forces with deployment-related posttraumatic stress symptoms - Niemeyer, Helen; Knaevelsrud, Christine; Schumacher, Sarah; Engel, Sinha; Küster, Annika; Burchert, Sebastian; Muschalla, Beate; Weiss, Deborah; Spies, Jan; Rau, Heinrich; Willmund, Gert Dieter (BMC Psychiatry, 2020)
Background The present study was designed to evaluate the efficacy of a therapist-guided internet-based cognitive-behavioral therapy (iCBT) intervention for service members of the German Armed Forces with posttraumatic stress disorder (PTSD). The iCBT was adapted from Interapy, a trauma-focused evidence-based treatment based on prolonged exposure and cognitive restructuring. It lasted for 5 weeks and included 10 writing assignments (twice a week). The program included a reminder function if assignments were overdue, but no multimedia elements. Therapeutic written feedback was provided asynchronously within one working day. Methods Male active and former military service members were recruited from the German Armed Forces. Diagnoses were assessed with the Clinician-Administered PTSD Scale for DSM-5 (CAPS-5) and the Mini-International Neuropsychiatric Interview. Psychopathology was assessed at pre-treatment, post-treatment, and 3-month follow-up. Severity of PTSD was the primary outcome and anxiety was the secondary outcome. Participants were randomly allocated to a treatment group that received iCBT immediately or to a waitlist group that received iCBT after 6 weeks. Due to the overall small sample size (n = 37), the two groups were collapsed for the statistical analyses. Change during the intervention period was investigated using latent-change score models. Results Improvements in the CAPS-5 were small and not statistically significant. For anxiety, small significant improvements were observed from pre- to follow-up assessment. The dropout rate was 32.3%. Conclusions The low treatment utilization and the high dropout rate are in line with previous findings on treatment of service members. The interpretation of the current null results for the efficacy of iCBT is limited due to the small sample size, however for military samples effect estimates were also smaller in other recent studies. Our results demonstrate the need to identify factors influencing treatment engagement and efficacy in veteran